Exploring the Visual Landscape - Advances in Physiognomic Landscape Research in the Netherlands - R. van Lammeren (ed.) (Research in Urbanism Series, 2011)
Exploring the Visual Landscape is about the combination of landscape research and planning, visual perception and Geographic Information Science. It showcases possible ways of getting a grip on themes like: landscape openness, cluttering of the rural landscape, high-rise buildings in relation to cityscape, historic landscapes and motorway panoramas. It offers clues for visual landscape assessment of spaces in cities, parks and rural areas. In that respect, it extends the long tradition in the Netherlands on physiognomic landscape research and shows the state of the art at this moment. Exploring the Visual Landscape offers important clues for theory, methodology and application in research and development of landscapes all over the world, from a specifically Dutch academic context. It provides a wide range of insights into the psychological background of landscape perception, the technical considerations of geomatics and methodology in landscape architecture, urban planning and design. Furthermore, there are some experiences worthwhile considering, which demonstrate how this research can be applied in the practice of landscape policy making.